Development and Evaluation of Isothermal Amplification Methods for Rapid Detection of Lethal Amanita Species - He, Zhengmi; Su, Yuting; Li, Sainan; Long, Pan; Zhang, Ping; Chen, Zuohong (Frontiers in Microbiology, 2019)
In the present work, loop-mediated isothermal amplification (LAMP) and hyperbranched rolling circle amplification (HRCA) methods were developed to detect and distinguish different lethal Amanita species. Specific LAMP primers and HRCA padlock probes for species-specific identification and a set of universal LAMP primers for lethal Amanita species were designed and tested. The results indicated that the LAMP-based assay was able to discriminate introclade lethal Amanita species but was not able to discriminate intraclade species perfectly, while the HRCA-based assay could discriminate whether introclade or intraclade species. The universal LAMP primers were positive for 10 lethal species of Amanita section Phalloideae and negative for 16 species of Amanita outside section Phalloideae. The detection limits of LMAP and HRCA were 10 pg and 1 pg of genomic DNA per reaction, respectively. In conclusion, the two methods could be rapid, specific, sensitive and low-cost tools for the identification of lethal Amanita species.